2000
DOI: 10.1002/(sici)1097-4628(20000620)76:12<1746::aid-app4>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Ternary blends of high-density polyethylene-polystyrene-poly(ethylene/butylene-b-styrene) copolymers: Properties and orientation behavior in plane-strain compression

Abstract: Ternary blends of high-density polyethylene (HDPE) with atactic polystyrene (PS) and styrene-ethylene/butylene-styrene block copolymer (SEBS) were deformed by plane-strain compression in a channel die. The samples were deformed up to the true strain of 1.8 (compression ratio of 6) at 100°C. Thermal and mechanical properties of the deformed blends were studied in addition to the study of the deformation process. The basic mechanism of plastic deformation is crystallographic slip, the same as that active in defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…It can be noticed that in PE/PS blends, PE has lower melting points Tm than alone. This is in good agreement with the work of Bartczak (18) 2 4 1 -0 4 1 -3 4 1 -9 3 1 -8 4 1 -5 3 1 -E P m T (°) C 4 3 1 7 3 1 4 3 1 0 3 1 1 3 1 9 2 1 observed that the crystallisation temperature of PE in PE/PS blends was increased in comparison with neat PE. As there are no significant differences between the polluted and the virgin blends, it can be concluded that the pollutants have little influence or no influence on the rate and the size of the crystals considered.…”
Section: Effect Of the Pollutants On The Crystallinity Of Blendssupporting
confidence: 90%
“…It can be noticed that in PE/PS blends, PE has lower melting points Tm than alone. This is in good agreement with the work of Bartczak (18) 2 4 1 -0 4 1 -3 4 1 -9 3 1 -8 4 1 -5 3 1 -E P m T (°) C 4 3 1 7 3 1 4 3 1 0 3 1 1 3 1 9 2 1 observed that the crystallisation temperature of PE in PE/PS blends was increased in comparison with neat PE. As there are no significant differences between the polluted and the virgin blends, it can be concluded that the pollutants have little influence or no influence on the rate and the size of the crystals considered.…”
Section: Effect Of the Pollutants On The Crystallinity Of Blendssupporting
confidence: 90%
“…The addition of a few wt% block copolymer for the emulsification and enhancement of mechanical properties of such immiscible polymer blends is well known 3–8. In order for the block copolymer to be effective in these roles, it must first of all be interfacially active.…”
Section: Introductionmentioning
confidence: 99%
“…When SEBS-g-MA is located at the interface between PS and HDPE, the styrene blocks of SEBS-g-MA is miscible with PS, while the hydrogenated ethylene-butadiene blocks could form entanglements with the HDPE phases. Previously the thermal behaviour of PS/HDPE blends was investigated, and it was found that the compatibilizer decreased the crystallinity of HDPE [44,62,73] due to the dilution with ethylene-butadiene segments of SEBS. Abis et al [70] mentioned that binary PS/HDPE blends did not show any changes in their DSC parameters, addition of 10% compatibilizer resulted in a decrease of the crystallization and melting temperatures, which indicated the compatibilization effect.…”
Section: Morphologymentioning
confidence: 99%
“…Some research mentioned styrene-butadiene copolymer (SB) [53] and styrene/butadiene/styrene block copolymer (SBS) [52] as a potential additive for compatibilizing PS and PE with each other, in other papers the effectiveness of polyether copolymer (PEC) [54], hydrogenated butadiene-polystyrene copolymers (SEB) [55] and ethylene/styrene interpolymers [47] were also investigated. However, the most commonly used compatibilizer for improving the miscibility of PS and PE is styrene/ethylene/butylene/styrene block copolymer (SEBS) and its maleic anhydride grafted type (SEBS-g-MA), with which adhesion can be improved between the phases to prepare blends with better toughness [35,44,45,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73].…”
Section: Introductionmentioning
confidence: 99%